EVALUATING VISUAL MERCHANDISE OF GAUDI MANADO TOWN SQUARE BY USING IMPORTANCE AND PERFORMANCE ANALYSIS - Sanger, Rini .; Lambey, Linda .; Pandowo, Merinda . (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Fashion industry has become a significant driver in Indonesia’s creative economy. Fashion industry is one of the exciting industries in Indonesia with no exception in Manado, PT. Dwi Laras Gaudi is a company engaged in the fashion industry. In connection with the fashion competition that occurs in Manado, marketers must be able to act creatively in the development. Visual merchandise is the only effective way of differentiating in fashion industry. Visual merchandising is the presentation of a store and its merchandise in such a manner that will attract the attention of potential customers. The aim of this study is to evaluate the importance and performance of visual merchandise attributes such as window display, mannequin, signage, store layout, color and lighting. This research is casual type of research, which uses primary data obtained through questionnaires and uses importance and Performance Analysis. 100 respondents are the sample size of this research. The result of this study shows that window display placed in quadrant I (very important but low performance), signage and lighting placed in quadrant II (very important and high performance), while mannequin, store layout and color placed in quadrant III (low importance and low performance).Keywords: visual merchandise, window display, mannequin, signage, store layout, lighting, color, importance and performance analysis.